2022
DOI: 10.3390/ijerph192316052
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy of People with Intellectual Disabilities: How Meaningful Is the Social Context for a Target Group-Oriented Model of Health Literacy?

Abstract: Health literacy is primarily understood as an individual construct. People with intellectual disabilities still seem to be a “hidden” population in health literacy research. A target-orientated health literacy approach for this population is needed for developing precise and effective interventions that consider social context dimensions. Therefore, the following research question was answered: Which dimensions influence the health literacy of people with intellectual disabilities? A secondary data analysis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Recent research has highlighted factors influencing health literacy for people with intellectual disability (Vetter et al . 2022) and identified approaches to improving health literacy for this population (e.g. modification of communication strategies, utilising multi‐modal methods), family and support workers (Latteck and Bruland 2020; Dam et al .…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has highlighted factors influencing health literacy for people with intellectual disability (Vetter et al . 2022) and identified approaches to improving health literacy for this population (e.g. modification of communication strategies, utilising multi‐modal methods), family and support workers (Latteck and Bruland 2020; Dam et al .…”
Section: Discussionmentioning
confidence: 99%
“…Studies highlighted in this Special Issue intersect with a broad diversity of research traditions on health literacy and social contexts. Vetter et al's (2022) [49] work contributed to the research tradition focused on defining health literacy in social contexts and did so for individuals with mild to moderate intellectual disabilities in Germany. Using 38 guided interviews, they found that health literacy is defined and shaped by multiple levels of social context, including educational settings, interpersonal relationships, organizational and social structures, the healthcare system, politics, cultural contexts, and digital interaction spaces.…”
Section: Health Literacy and Social Context Findings From The Special...mentioning
confidence: 99%
“…Given the strong evidence that health literacy leads to better healthcare outcomes, the health literacy field has continued to explore the health literacy of people with disabilities including people with intellectual disabilities (Geukes et al, 2019; Vetter et al, 2022), visual disabilities (Fortuna, 2021; Harrison et al, 2012; Schwennesen et al, 2019) and hearing disabilities (Gur et al, 2020). Literature reviews have also been conducted on the health literacy of people with disabilities, but they have mostly focused on a particular disability or on exploring issues related to health literacy (Beverley et al, 2004; Chinn, 2017; Geukes et al, 2019; Harrison et al, 2010; Mastebroek et al, 2014; Turnbull et al, 2022; Vetter et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Given the strong evidence that health literacy leads to better healthcare outcomes, the health literacy field has continued to explore the health literacy of people with disabilities including people with intellectual disabilities (Geukes et al, 2019;Vetter et al, 2022), visual disabilities (Fortuna, 2021;Harrison et al, 2012;Schwennesen et al, 2019) and hearing disabilities (Gur et al, 2020).…”
Section: Introductionmentioning
confidence: 99%